Analysis of citizens’ awareness in the issues of posthumous corneal donation - N. I. Vishnyakov; P. I. Konstantinova; L. V. Kochorova; K. S. Klyukovkin; A. A. Kozyrev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
The objective was to analyze the views of citizens of the Russian Federation on a number of issues related to donation and transplantation of a cadaveric cornea.Methods and materials. In order to conduct a sociological survey of citizens, we have developed a questionnaire that includes a number of questions concerning the topics of donation and transplantation. The total volume of the study was 768 observation units. Results. Most of the respondents had a positive attitude towards posthumous donation. Almost all respondents knew about the existence of queues for organ transplantation, and also generally agreed with the opinion that informational popularization of posthumous donation should be carried out. The overwhelming majority of respondents believe that it is mandatory to have an informed consent during their lifetime, but some of them allow an operation to remove organs without such consent in some cases. Conclusion. Given the lack of knowledge about posthumous donation, there is a need to carry out sanitary and educational work among the population, revealing in detail all the main provisions related to posthumous donation.